Is the Ethiopian Boran breed under threat? Observations on morphological variables at Adamitulu Research Centre and Abernosa Ranch - Alemayehu, Nigatu (2001)
An observational study was conducted on a total of 22 discrete and continuous morphological variables of two herds of Ethiopian Boran cattle maintained at the Adamitulu Research Centre and Abernosa Ranch Eastern Shoa Zone, Oromyia Regional State, Ethiopia from 8 to 18 August, 2001. The animals were classified into two groups based on the lenbgth of their stay in the herds as foundation (>= 15 years) and replacement ( < 15 years). Similarly they were grouped into typical and variant forms of the Ethiopian Boran cattle based on subjective judgment of experienced herd attendants. Comparison of these measurements was made between animal groups of different origins, batches and location. Linear body measurements were found to be significantly different between batches of animals (foundation and replacement stocks), origins and locations. Animals identified as typical Boran were also markedly different in these linear measurements than the groups of animals identified as variants. Measurements (in cm) on mature Boran of the typical type were found to be 102 +_7.2, 118.3 +_ 5.2, 170.2 +_ 9.3, 20.3+_ 2.3 and 10.4+_ 5.1 for body length, height at withers, heart girth, ear length and horn length, respectively. In the same order, the variant types measured 96.6 +_ 5.9, 114.5 +_5.7, 158.8 +_ 10.3, 18.5 +_2.4 and 12.3+_5.4. The differences in the values between the typical and variant types were highly significant (P <0.001). Similarly animals of the foundation stock had significantly higher values (P < 0.05) than the replacements. The results showed that animals of different batches have undergone different levels of morphological changes, strengthening the need for genetic conservation of the Ethiopia Boran breed. They also demonstrate genetic diversity even within a breed.